Indonesia’s contribution in tracing the human ancestor - Fachroel Aziz (Ikatan Ahli Geologi Indonesia, 2021)
Since Darwin’s postulated the origin of the human species from an ape-like ancestor, the search for the missing link between ape and human had begun. In 1887, Eugene Dubois traveled from the Netherlands to Indonesia to search for the missing link. He eventually discovered human fossils in Wajak, Kedungbrubus, and Trinil to which he named Pithecanthropus erectus. The research was then continued by Ter Haar (1931) in Ngandong, Dujfyes, and his assistant, Andoyo (1936) in Perning, Mojokerto, and Von Koenigswald (1936-1940) in Sangiran, who successfully discovered many Homo erectus fossils. Since the 1960s, Sartono (ITB), T. Jacob (UGM), and Geological Research and Development Centre (Indonesia) continue the study, adding the collection of the specimens. Collaboration with the National Museum of Science and Nature, Tokyo concluded that Indonesian Homo erectus went through local evolution instead of static evolution condition. Indonesia is rich in natural resources and environmental conditions that were suitable for the evolution of early humans as shown by the discovery of several Homo erectus skeleton fossils that were not found in most other countries. This is a blessing left by early humans to us.